Anomaly of the Death of Polling Station Committee Members (KPPS) during 2019 Elections in Pekanbaru - Husni Setiawan; Afridelma Dwi Putri; Suriati Suriati; Novita Novita; Ridho Mardhianto (JOELS: Journal of Election and Leadership, 2020)
This study discusses the death of 15 KPPS members in Riau Province in election 2019. The death of KPPS members massively raised questions for the public. This study aims to describe and analyze the cause of death of 15 KPPS officers. This study used a descriptive qualitative approach by analyzing the data ethically and emic. This study used institutional analysis with the key informant is General Election Commission (KPU) Riau. The findings of this study are: First, the recruitment process of KPPS members has conducted under the technical guidelines for recruitment but does not have regular standards. Second, the death of 15 KPPS members caused due to exhausted and had a history of internal medicine. Third, the victim is given compensation by the government by established regulations.